Photocatalytic, magnetic, and electrochemical properties of La doped BiFeO3 nanoparticles. Issue 16 (November 2018) - Reddy, B. Purusottam; Sekhar, M. Chandra; Prakash, B. Poorna; Suh, Youngsuk; Park, Si-Hyun
Abstract: We successfully prepared La1− x Bi x FeO3 (L x B1− x FO, x  = 0.01–0.1) nanoparticles using a sol-gel technique, and studied their photocatalytic, magnetic, and electrochemical properties. Structural refinement studies of the prepared nanoparticles revealed a gradual structural transition from rhombohedral to orthorhombic. The average grain size was observed to decrease with increasing the concentration of La. The photocatalytic degradation of Rhodamine B (RhB) in the presence of the prepared nanoparticles was studied under visible light irradiation. The L0.06 B0.94 FO nanoparticles showed higher degradation efficiency compared to pure BiFeO3 (BFO) nanoparticles. Magnetic studies showed that La doping improved the magnetization of BFO due to the reduction in grain size and destruction of cycloid coupling of spins. Higher specific capacitance values were obtained for La doped BFO (LBFO) nanoparticles compared to BFO nanoparticles. A maximum specific capacitance of 219 F g −1 was obtained at a current density of 1 A g −1 for LBFO nanoparticles.